2003
DOI: 10.1046/j.1365-2486.2003.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in carbon storage and fluxes in a chronosequence of ponderosa pine

Abstract: Forest development following stand‐replacing disturbance influences a variety of ecosystem processes including carbon exchange with the atmosphere. On a series of ponderosa pine (Pinius ponderosa var. Laws.) stands ranging from 9 to> 300 years in central Oregon, USA, we used biological measurements to estimate carbon storage in vegetation and soil pools, net primary productivity (NPP) and net ecosystem productivity (NEP) to examine variation with stand age. Measurements were made on plots representing four age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
286
6
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(334 citation statements)
references
References 30 publications
38
286
6
4
Order By: Relevance
“…Figure 3 shows the estimated T ABC increased continuously with forest stand age across all four forest types in the two time periods, 1994-1998 and 1999-2003, respectively. Previous studies had reported T ABC maintained a balance or slight decline in mature and old forest stages [15][16][17], but this study found a significant increase of T ABC between mature and old stages (Figure 3). The differences of T ABC among all age stages were significant (P < 0.01) for the four forest types (Figure 3).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Figure 3 shows the estimated T ABC increased continuously with forest stand age across all four forest types in the two time periods, 1994-1998 and 1999-2003, respectively. Previous studies had reported T ABC maintained a balance or slight decline in mature and old forest stages [15][16][17], but this study found a significant increase of T ABC between mature and old stages (Figure 3). The differences of T ABC among all age stages were significant (P < 0.01) for the four forest types (Figure 3).…”
Section: Discussioncontrasting
confidence: 79%
“…A number of studies on tree growth indicate plant biomass increases with forest stand age, and reaches an equilibrium or declines slightly in mature and old stages [15][16][17]. However, increasing amounts of soil organic carbon were found in many old-growth forests [3].…”
Section: Reliability Of Logistic Regression As a Proxy For Carbon Seqmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of precipitation changes on individual plant performance are complex and depend on a number of factors, such as ambient rainfall conditions, initial soil water status, occurrence and seasonality of extreme heat stress or droughts (De Boeck et al 2011), plant age (Law et al 2003), the ability of the plant to shed wilted leaves (Chaves et al 2009), and the diversity of the surrounding plant community (Kahmen et al 2005). Previous studies have found that the photosynthetic responses of grassland plants to rainfall manipulations simulating drought conditions have ranged from negative to neutral (reviewed in Fay et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Trees invest a larger proportion of NPP into aboveground tissue production as conditions become wetter and competition for light intensifies (Runyon et al, 1994;Law et al, 2003). Our field measurements suggested that the fraction of NPP allocated aboveground increased from ∼ 0.45 in the driest areas to ∼ 0.64 in the wettest areas and, furthermore, that CRT in aboveground tissues averaged twice as long as CRT in belowground tissues.…”
Section: Carbon Residence Time In Tree Biomassmentioning
confidence: 64%